How do you solve #3(2x - 1) - 2(3x +4) = 11x#?

3 Answers
May 26, 2018

Answer:

#x=-1#

Explanation:

Expanding
#6x-3-6x-8=11x#
This gives
#-11=11x#
#x=-1#

May 26, 2018

Answer:

#x=-1#

Explanation:

#3(2x-1) =6x-3#

#2(3x+4) = 6x+8#

So

#6x-3 -(6x+8)=11x#

#6x-3-6x-8 =11x#

#-3-8=11x#

#-11 =11x#

This gives

#(-11)/11 =(11x) /11#

#x=-1#

May 26, 2018

Answer:

#x=-1#

Explanation:

Expand your brackets first...

#3(2x-1)=6x-3#
#-2(3x+4)=-6x-8#

This give you...

#6x-3-6x-8=11x#

Then you move all the like terms to each sides...

#-3-8=11x+6x-6x#

Then simplfy by cancelling out like terms...

#-11=11x#

#x=-11/11#

#x=-1#